TEACHER’S SCAFFOLDING IN TEACHING WRITING REPORT TEXT - Hijriati Utami Putri (Journal of English Education Program (JEEP), 2016)
This paper discusses about the successful use of scaffolding techniques to improve students’ writingskills in Junior High School. This study  is aimed at finding how the teacher uses scaffolding in teaching writing report text and finding kinds of scaffolding which are used by the teacher in teaching writing report text. The population of this study is all English teacher and all of students at the ninth grade at SMP N 3 Kawali that consisted of one hundred and twenty five students. This study used purposive sampling. Therefore, the writer took one class of the ninth grade students and one of  English teacher  as a sample of the study. Furthermore, the writer conducted a case study and used classroom observation to observed how the teacher taught writing report text including the techniques she used and the interaction between the teacher and the students. The interview guideline was used to notice the kind of scaffolding which are used by teacher in teaching  writing report text. The result and finding of this study includes that the scaffolding techniques involved modeling the concepts and expected behavior by the instructor, conducting in-class activities to help students learn the concepts, assigning homework activities that build on the previous steps, and providing clarifications and support resources to help students in the learning process. It can be concluded that the scaffolding techniques allowed students to go from simple to complex aspects of writing, such as grammar, vocabulary and the writing process,  and develop the necessary writing skills and confidence in their abilities without assistance.